The existence of street vendors (PKL) as supporting activities in Jalan Taman Siswa, Semarang - Pratiwi, Isna; Sari, Suzanna Ratih; Sardjono, Agung Budi (Semarang State University, 2018)
Sekaran area has rapidly developed nowadays, especially the development of street vendors’ existence asthe facility of fulfilling students’ needs from the very first establishment of Unnes. There is not only street vendors’phenomenon but also there exist change of land function, the development of building and traffic density. Severaladditional activities to the developed area would relatively increase such impacts towards street vendor developmentin Sekaran, especially in Jalan Taman Siswa. This phenomenon is interesting to be studied because a part of JalanTaman Siswa becomes one of the important corridors in Semarang State University area. This corridor,unfortunately, has been changed into the center of street vendors.The data collecting employed by the writer wasobservation, interview, and documentation. This study employs qualitative approach. Whereas the method used isdescriptive design. By implementing this method, the writer will elaborate the problems appeared briefly andcomprehensively. Theoretical data are collected by reviewing the related literature, which means that the writergathers the data by reading much relevant literature. This data is managed by conducting analysis and applying thedata to the study. The existence of Unnes as one of the big campuses in Semarang triggers the occurrence of severalstudents' activities such as to fulfill students' daily necessity. Along Kinanti boarding house to Ulul Albab Mosque,there exist several supporting facilities for Unnes students and people around the campus. This is interesting sincethe occurrence of supporting activity such as PKL in that area has the strong relationship with the use of publicspaces. Thus, it could be formulated that the presence of PKL as activity support in Taman Siswa corridor increasesalong with the development of Semarang State University Campus.